ZORA 155: Poglavja o različicah slovenskega jezika - Jesenšek, Marko (University of Maribor Press, 2024)
ZORA 155: Chapters on the Varieties of the Slovene Language. The monograph Chapters on the Varieties of the Slovene Language is the twelfth independent book by Marko Jesenšek, the leading scholar and no doubt the best expert on the history of the Slovene literary language and its regional varieties today. The book contains discussions and articles on the dual development of the Slovene language. It consists of five parts, further divided into eighteen chapters: (1) Slovene literary varieties and the unification of the literary norm, (2) the Carniolian literary language, (3) the Prekmurje literary language, (4) the Easteren Styrian regional (literary) variety, and (5) the Unified Slovene literary language. It focuses on the question of the normativity and dialectality of the Slovene language, which until the mid-19th century had two literary versions. The main scientific insight of the monograph is that the literary Prekmurje language was formed in the same way as the literary Carniolian language, namely as a by-product of Slovene Protestantism.